The Lerch zeta-function with algebraic irrational parameter - Genienė, Danutė (Lietuvos matematikos rinkinys, 2009)
In this note, we present probabilisticlimit theorems on the complex plane as well as in functional spaces for the Lerch zeta-function with algebraic irrational parameter.
Keywords: Lerch zeta-function; probability measure; weak convergence